Clustering Residents’ Perception of Rural Rally Tourism: An Inclusive Approach from the Sierra Morena Rally in Obejo, Spain - José E. Ramos-Ruiz; Jesyca Salgado-Barandela (Tourism and Hospitality)
Motorsports tourism has a significant impact on host communities, especially when they are small communities. This research aims to segment the resident population of a very small rural municipality, Obejo, before the celebration of the Sierra Morena Rally in the province of Cordoba, Spain. The study is based on the principles of social exchange theory (SET) and the triple bottom line (TBL). In addition, it follows calls from the existing academic literature to explore a fourth dimension of impact perception, related to inclusion from the point of view of gender, age, and functional diversity. exploratory factor analysis (EFA) and non-hierarchical cluster analysis were used on a sample of 281 residents. A structure of four dimensions of impact perception is obtained: economic, social, environmental, and inclusive. Together, they explain just over 80% of the total variance. Three population segments are defined: motor enthusiasts, environmentally conscious fans, and admitted critics. This study underlines the need to expand the TBL framework with an inclusive dimension in motorsports tourism, emphasizing gender equality, intergenerational participation and functional diversity to foster more sustainable and socially cohesive events in rural areas.